Community Empowerment Through Motivational Seminars to “Prepare for College” Life at SMA Negeri 1 Jabiren Raya - Ahmad Robi Ul'zikri; Ari Jhon Peter; Eko Rianto; Yuyung Yuyung; Efrian Kurniawan; Jossy Viandre; Ksatria Valent; Samuel Lin Shing Lee; Mas Alfuzi Febrianto; Moh Naufal Azhar Khoiri; Yogy Andika Rachman (PT Polstac Repositori Riset, 2026)
Background: The community empowerment activity with the theme “Preparing Yourself for College” aims to improve the readiness of high school/vocational school students in facing the transition to higher education. Contribution: This program is implemented through a series of activities such as motivational seminars, learning skills training, campus orientation, and assistance in choosing a study program according to interests and talents Method: The implementation method uses a participatory approach by involving students, teachers, and community leaders as facilitators Results: The results of the activities show an increase in participants' understanding of the adaptation process in the world of college, increased motivation to learn, and awareness of the importance of academic planning and soft skills development. Conclusion: Thus, this activity is expected to become a model for sustainable empowerment that helps prospective students adapt academically and socially in college